2014
DOI: 10.1039/c3tc31393j
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of sulfide stabilized colloidal semiconductor nanocrystals

Abstract: The effect of thermal annealing on layers of CuInS2 nanocrystals (NCs) stabilized with (NH4)2S was investigated using in situ transmission electron microscopy (TEM), in situ X-ray diffraction (XRD), thermogravimetric analysis combined with mass spectrometry (TGA-MS) and X-ray photoelectron spectroscopy (XPS). It is shown that these inorganic, chalcogen containing ligands inhibit NC sintering up to 450 °C in an inert atmosphere. On the other hand, sintering can be promoted by annealing in hydrogen gas. A simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Many strategies have been carried out for improving the morphology of the blend lms, such as the selection of solvent, 9 solvent additive, 21 using mixed solvents, 22 solvent vapor and thermal annealing treatments. [23][24][25] However, the morphology of active layer including narrow band gap polymer is hardly adjusted by thermal annealing treatment due to its poor self-packaging characteristic. 26,27 Recently, Liang et al reported an efficient method to adjust the active layer morphology by adopting mixed solvent approach.…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been carried out for improving the morphology of the blend lms, such as the selection of solvent, 9 solvent additive, 21 using mixed solvents, 22 solvent vapor and thermal annealing treatments. [23][24][25] However, the morphology of active layer including narrow band gap polymer is hardly adjusted by thermal annealing treatment due to its poor self-packaging characteristic. 26,27 Recently, Liang et al reported an efficient method to adjust the active layer morphology by adopting mixed solvent approach.…”
Section: Introductionmentioning
confidence: 99%
“…To get a better overview on the crystal growth, we used the Scherrer equation to estimate the crystallite size after annealing from the width of the diffraction peaks. Table 2 summarizes the results for the three studied systems containing excess selenium and compares them to previous results obtained by simply annealing the as-synthesized CIS NCs [23]. The data clearly show the additional sintering effect imparted by selenization.…”
Section: Resultsmentioning
confidence: 72%
“…The synthesis of CuInS 2 NCs is based on a previously described literature procedure [23,24]. Cu(acac) 2 (1 mmol) and In(acac) 3 (1 mmol) are mixed together with S (2.05 mmol) and ODE (14 ml).…”
Section: Precursor Synthesismentioning
confidence: 99%
“…Further, during annealing or selenization, the DAS ligand could simply volatilize as ammonia and hydrogen sulfide gas. 46 A two-phase ligand exchange was employed as is common in the literature. 35 First, the nanoparticles were dispersed in nonpolar hexanes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%